Responder
Here are the solutions to the equations:
1. \( x = 3 \)
2. \( x = 6 \)
3. \( x = 4 \)
4. \( x = -2 \)
5. \( x = -9 \)
6. \( x = 13 \)
7. \( x = 5 \)
8. \( x = -8 \)
9. \( x = -2 \)
10. \( x = -14 \)
11. \( x = 1 \)
12. \( x = -7 \)
13. \( x = -3 \)
14. \( x = 18 \)
15. \( x = -21 \)
16. \( x = -7 \)
17. \( x = 10 \)
18. \( x = 3 \)
Solución
Sure, let's solve each of the given linear equations step by step.
---
### **(1) \( 5x + 6 = 2x + 15 \)**
\[
\begin{align*}
5x + 6 &= 2x + 15 \\
5x - 2x &= 15 - 6 \\
3x &= 9 \\
x &= \frac{9}{3} \\
x &= 3
\end{align*}
\]
**Solution:** \( x = 3 \)
---
### **(2) \( 7x - 4 = 20 + 3x \)**
\[
\begin{align*}
7x - 3x &= 20 + 4 \\
4x &= 24 \\
x &= \frac{24}{4} \\
x &= 6
\end{align*}
\]
**Solution:** \( x = 6 \)
---
### **(3) \( 2x + 15 = 43 - 5x \)**
\[
\begin{align*}
2x + 5x &= 43 - 15 \\
7x &= 28 \\
x &= \frac{28}{7} \\
x &= 4
\end{align*}
\]
**Solution:** \( x = 4 \)
---
### **(4) \( 3 + 4x = 9x + 13 \)**
\[
\begin{align*}
3 - 13 &= 9x - 4x \\
-10 &= 5x \\
x &= \frac{-10}{5} \\
x &= -2
\end{align*}
\]
**Solution:** \( x = -2 \)
---
### **(5) \( 2x - 10 = 44 + 8x \)**
\[
\begin{align*}
2x - 8x &= 44 + 10 \\
-6x &= 54 \\
x &= \frac{54}{-6} \\
x &= -9
\end{align*}
\]
**Solution:** \( x = -9 \)
---
### **(6) \( -7x - 2 = 24 - 9x \)**
\[
\begin{align*}
-7x + 9x &= 24 + 2 \\
2x &= 26 \\
x &= \frac{26}{2} \\
x &= 13
\end{align*}
\]
**Solution:** \( x = 13 \)
---
### **(7) \( 27 - 11x = x - 33 \)**
\[
\begin{align*}
27 + 33 &= x + 11x \\
60 &= 12x \\
x &= \frac{60}{12} \\
x &= 5
\end{align*}
\]
**Solution:** \( x = 5 \)
---
### **(B) \( 21x + 6 = 17x - 26 \)**
\[
\begin{align*}
21x - 17x &= -26 - 6 \\
4x &= -32 \\
x &= \frac{-32}{4} \\
x &= -8
\end{align*}
\]
**Solution:** \( x = -8 \)
---
### **(9) \( 11x = 8x - 6 \)**
\[
\begin{align*}
11x - 8x &= -6 \\
3x &= -6 \\
x &= \frac{-6}{3} \\
x &= -2
\end{align*}
\]
**Solution:** \( x = -2 \)
---
### **(10) \( -x - 29 = 13 + 2x \)**
\[
\begin{align*}
-x - 2x &= 13 + 29 \\
-3x &= 42 \\
x &= \frac{42}{-3} \\
x &= -14
\end{align*}
\]
**Solution:** \( x = -14 \)
---
### **(11) \( -18 + 5x = -12x - 1 \)**
\[
\begin{align*}
5x + 12x &= -1 + 18 \\
17x &= 17 \\
x &= \frac{17}{17} \\
x &= 1
\end{align*}
\]
**Solution:** \( x = 1 \)
---
### **(12) \( -9x - 21 = 35 - x \)**
\[
\begin{align*}
-9x + x &= 35 + 21 \\
-8x &= 56 \\
x &= \frac{56}{-8} \\
x &= -7
\end{align*}
\]
**Solution:** \( x = -7 \)
---
### **(13) \( 7x - 2 = -2x - 29 \)**
\[
\begin{align*}
7x + 2x &= -29 + 2 \\
9x &= -27 \\
x &= \frac{-27}{9} \\
x &= -3
\end{align*}
\]
**Solution:** \( x = -3 \)
---
### **(14) \( 36 + 15x = 17x \)**
\[
\begin{align*}
36 &= 17x - 15x \\
36 &= 2x \\
x &= \frac{36}{2} \\
x &= 18
\end{align*}
\]
**Solution:** \( x = 18 \)
---
### **(15) \( -15 - 4x = 6 - 3x \)**
\[
\begin{align*}
-4x + 3x &= 6 + 15 \\
-x &= 21 \\
x &= -21
\end{align*}
\]
**Solution:** \( x = -21 \)
---
### **(16) \( 12x - 9 = 8x - 37 \)**
\[
\begin{align*}
12x - 8x &= -37 + 9 \\
4x &= -28 \\
x &= \frac{-28}{4} \\
x &= -7
\end{align*}
\]
**Solution:** \( x = -7 \)
---
### **(17) \( -5x + 40 = 6x - 70 \)**
\[
\begin{align*}
-5x - 6x &= -70 - 40 \\
-11x &= -110 \\
x &= \frac{-110}{-11} \\
x &= 10
\end{align*}
\]
**Solution:** \( x = 10 \)
---
### **(18) \( -x - 2 = 1 - 2x \)**
\[
\begin{align*}
-x + 2x &= 1 + 2 \\
x &= 3
\end{align*}
\]
**Solution:** \( x = 3 \)
---
### **Summary of Solutions:**
1. \( x = 3 \)
2. \( x = 6 \)
3. \( x = 4 \)
4. \( x = -2 \)
5. \( x = -9 \)
6. \( x = 13 \)
7. \( x = 5 \)
8. \( x = -8 \) *(Originally labeled as (B))*
9. \( x = -2 \)
10. \( x = -14 \)
11. \( x = 1 \)
12. \( x = -7 \)
13. \( x = -3 \)
14. \( x = 18 \)
15. \( x = -21 \)
16. \( x = -7 \)
17. \( x = 10 \)
18. \( x = 3 \)
---
Feel free to reach out if you have any further questions or need additional explanations!
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución